Three urban areas of China: a cohort study of maternal–infant factors and HM protein components. Issue 9 (19th April 2022) - Chen, Jingyao; Liu, Yan; Zhao, Junying; Jiang, Tiemin; Xu, Tao; Liu, Bin; Liu, Yanpin; Yang, Baoyu; Li, Ying; Zhang, Xiaomei; Hou, Juncai; Chen, Lijun
Abstract : This work studies the concentrations of proteins in human milk (HM) at different lactation periods and explores the influence of maternal–infant factors on the dynamics of HM proteins in a Chinese cohort. Abstract : This work studies the concentrations of proteins in human milk (HM) at different lactation periods and explores the influence of maternal–infant factors on the dynamics of HM proteins in a Chinese cohort. The cohort contained 153 mother–infant pairs, and 12 main proteins of 376 HM samples were analyzed. The result showed that physiological factors (age and pre-pregnancy BMI), demographic factors (education and occupation), endogenous factors (cesarean section), and exogenous factors (lactation period and area) could explain the dynamics of HM proteins, including the total protein, true protein, whey protein, β-casein, lactoferrin, IgA, and IgM ( R 2 > 0.3). Factor analysis explained the dynamic changes in the IgM content by the highest degree of 49.5%. This study aimed to find the mother–infant factors that affected the dynamic changes in HM proteins, in order to optimize HM proteins and improve the long- and short-term health of infants (registration number: NCT02658500).